2010
DOI: 10.1152/ajpregu.00866.2009
|View full text |Cite
|
Sign up to set email alerts
|

ID family protein expression and regulation in hypoxic pulmonary hypertension

Abstract: To address this, we evaluated pulmonary expression of ID proteins in a mouse model of hypoxia-induced PH. There is selective induction of ID1 and ID3 expression in hypoxic pulmonary vascular smooth muscle cells (VSMCs) in vivo, and ID1 and ID3 expression are increased by hypoxia in cultured pulmonary VSMCs in a BMPdependent fashion. ID4 protein is barely detectable in the mouse lung, and while ID2 is induced in hypoxic peripheral VSMCs in vivo, it is not increased by hypoxia or BMP signaling in cultured pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…These investigators reported that Id1 and 3 expression are increased by hypoxia in a BMP-dependent fashion in PASMCs. Id1 knockout mice did not develop more severe pulmonary hypertension during chronic hypoxic exposure than wild-type mice, which was thought to be due to the compensation by Id3 (14). Indeed, potential compensation of Id3 for Id1 is well recognized from studies in angiogenesis (30).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These investigators reported that Id1 and 3 expression are increased by hypoxia in a BMP-dependent fashion in PASMCs. Id1 knockout mice did not develop more severe pulmonary hypertension during chronic hypoxic exposure than wild-type mice, which was thought to be due to the compensation by Id3 (14). Indeed, potential compensation of Id3 for Id1 is well recognized from studies in angiogenesis (30).…”
Section: Discussionmentioning
confidence: 97%
“…The potential role of Id1 and 3 has been explored previously in the chronically hypoxic mouse model of pulmonary hypertension (14). These investigators reported that Id1 and 3 expression are increased by hypoxia in a BMP-dependent fashion in PASMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In opposition to these findings, Id3 was elevated in response to hypoxia. The different Id3 expression suggests that this family of transcription factors may act cooperatively in regulating BMP-dependent SMC proliferation due to chronic hypoxia (95). While the molecular signaling events are still unclear, the cyclin-dependent kinase inhibitor proteins, p21 and p27, appear to be the targets for Id proteins (96).…”
Section: Notch-3mentioning
confidence: 99%
“…This study revealed that one of the poorly differentiated types of OSCC cells expressed Id1 but that most of the differentiated types slightly expressed Id1 or not at all, with the exception of HSC-2. In this study, we examined the effects of Id1 and Id2 but not that of Id3, since Id3 usually mirrors the expression pattern of Id1 [27]. Moreover, Id4 was not examined because it is strongly associated with brain tumors.…”
Section: Discussionmentioning
confidence: 99%